Kanker Paru Berdasarkan Riwayat Paparan Rokok - Artanto, Kurniawan Ros; Riyadi, Sujono (Fakultas Ilmu Kesehatan, 2024)
Lung cancer is a condition whose exact cause is not yet known. There are various risk factors for lung cancer. However, a history of exposure to cigarettes is one of the main risk factors in lung cancer cases. The aim of the research was to understand the characteristics of lung cancer patients based on their history of exposure to cigarettes at Hospital on Yogyakarta in 2023. This research method is a Quantitative, descriptive; provides an overview of the characteristics of lung cancer patients based on history of exposure to cigarettes. Univariate; characteristics of lung cancer patients based on history of exposure to cigarettes, total sampling. Description of lung cancer patients at Hospital Yogyakarta in 2023. Results of examination of anatomical pathology specimens suspected of lung cancer from 129 patients with suspected lung cancer, there were 45.74% cases of lung cancer, 9.3% of other cancers, a combination of lung cancer and other cancers 0, 77% and non-cancer 44.18%. Lung cancer patients had a history of being active smokers 43.33% and had no history of being active smokers 56.67%. Characteristics of lung cancer patients based on history of exposure to cigarettes have almost the same pattern for most of the characteristics of both patients who have a history of exposure as active smokers and those who do not have a history of exposure as active smokers